Synthesis of luminescent nitroxobenzene oligomers by aluminum chloride catalyzed dehydration of nitrobenzene. (8th January 2016) - Wilcox, Robert J.; Folmer, Jacob C.W.; Kennemur, Justin G.; Martin, James D.
Graphical abstract: Under solvothermal reaction conditions, aluminum chloride catalyzes the polymerization of nitrobenzene yielding paramagnetic, luminescent materials. Proceeding through Wheland intermediates, a radical mechanism is proposed whereby a nitro oxygen atom and two aromatic hydrogens are lost to form water in the process of forming C–C and C–N polymer linkages. Abstract: Under solvothermal reaction conditions, nitrobenzene is heated in the presence of aluminum chloride to yield a luminescent and paramagnetic low molecular weight polymeric material along with AlCl3 ·(H2 O)6 . MALDI mass spectral analysis demonstrates that the repeat unit consists of the biphenyl moiety (ONC6 H3 –ONC6 H4 ). Four distinct fractions are isolated based on differential solubility characteristics. The primary differentiating features of these fractions appear to be their considerably different conjugation and branching characteristics. A radical mechanism, consistent with the formation of Wheland intermediates is proposed to account for the observed mass spec, IR, UV–Vis, EPR and size exclusion chromatographic data. Luminescence spectroscopy data is also provided demonstrating the white light emission exhibited by these polymers.